Factors Affecting Financial Performance of Life Insurance Sector in Pakistan - Ishtiaq, Nazish; Siddiqui, Danish Ahmed (International Journal of Social and Administrative Sciences, 2019)
The purpose of this research is to investigate the factors that affect the financial performance of the life insurance sector in Pakistan. Possible internal and external factors that include liquidity, net premium, and premium growth, underwriting risk, debt to equity, insurance leverage, tangibility, equity capital, capital surplus, Gross Domestic Product (GDP), inflation and market share have been used to assess their effect, whereas sector Return on Assets (ROA) has been used to assess the performance. The data has been gathered from 2008 to 2017 from 09 life insurance companies including 01 public and 08 private life insurance companies. In these observations, there are 02 companies that solely conduct their business on takaful life insurance while others are conventional based or both. Results have been analyzed using panel regression to panel the ordinary least square regression model and the generalized method of the moment is used to estimate the results. The outcome of this study shows that tangibility, market share, net premium, insurance leverage and GDP is insignificantly or negatively related to the financial performance of Pakistani Life Insurance Company, whereas, the other independent variables such as liquidity, underwriting risk, debt to equity, equity capital, capital surplus and inflation are positively and significantly related. This research should support the insurance industry in increasing their premium collecting activities and active participation in the market through increased awareness of life insurance to its beneficiary. The newcomers can also use this research as a beneficial survey for capturing the market. This research may also prove handy for the shareholders/investors and/or also for the insured to find out soundness and solvency of their insurer.